Normative Data for 111 Compound Remote Associates Test Problems in Romanian - Olteţeanu, Ana-Maria; Taranu, Mihaela; Ionescu, Thea (Frontiers in Psychology, 2019)
The Remote Associates Test (RAT) is a classical creativity test developed by Mednick and Mednick in 1967. RAT problems and their norms so far exist only in a few languages, including English, Dutch, Japanese and Italian. In this paper, we describe our process of constructing a set of Remote Associates Test problem in Romanian. 63 native speaking Romanian participants have solved this set. The set of items shows high internal consistency. Normative data pertaining to each problem is provided, together with a description of RAT problems peculiarities in Romanian.